Human Footprints on the Global Environment: Threats to Sustainability by Eugene A. Rosa, Andreas Diekmann, Thomas Dietz, & Carlo Jaeger (Eds.) - PAPE, JESSICA (ProQuest CSA, 2010)
The topic of global environmental change (GEC) is of urgent importance today. To address planetary scale problems like climate change, biodiversity loss, or overconsumption it is important to understand the causes and consequences of human impacts on GEC. In their edited collection Human Footprints on the Global Environment: Threats to Sustainability Eugene Rosa, Andreas Diekmann, Thomas Dietz, & Carlo Jaeger present a comprehensive overview of approaches to explaining and conceptualizing GEC. By presenting research from authors with different academic backgrounds, this collection aims to enhance the discourse on GEC across disciplinary boundaries by ?bridging future work in social and ecological sciences.? By focusing on the human impacts of GEC and the coupled impact of human and natural systems (CHANS), this multidisciplinary work manages to discuss such diverse topics as land use, risk societies, international regimes, common property, and vulnerability. The goal of the book is to ?bring together core findings on the human dimensions of GEC to illustrate the advances that have been made in this critical area of study? and to understand the complex challenges of CHANS in the context of environmental change.
Human Footprints on the Global Environment: Threats to Sustainability
PUBLISHED
Keywords: Geography; sustainability